STUDY OF DIMENSIONS OF FLOW STATE OF BADMINTON PLAYERS - Gurmeet Singh; Neeraj Malik (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
AbstractThis Study was conducted to know the present Flow State of the Indian Universities Badminton team which was going to participate in 26th Summer Universiade at Shenzen, China. And to know the relation between the flow and its dimensions based on the Flow State Scale -2 (Jackson & Eklund, 2004). For this study both the boys and girls teams were selected which consists of six members each. It was a survey designed study and Flow State Scale-2 (Jackson & Eklund, 2004) was used to gather data to calculate overall Flow and its dimensions. The information was gathered during the training camp before the team left for China. In both the teams the present flow state was at a significant level 4.23 (Girls) & 4.17 (Boys) and Overall flow and other dimensions yielded a significant positive correlation, for girls team flow yielded a significant positive correlation Merging (r = .76), Concentration (r = .85), Time (r = .89), Autotelic (r = .77). For boys team flow yielded a significant positive correlation Merging (r = 89), Goals (r = .74), Control (r = .82). So it can be concluded that both the teams are in a better Flow State when they left for the championship and above said dimensions are highly correlated with overall flow state of the players in both boys and girls.Keywords: Flow, Badminton players, Badminton